Does Haryana’s SHG Participation Help the Quality of Life of Dalit Women? An Approach Based on Composite Index and Treatment Effect - Kumari, Lalita; Dias, Rui; Irfan, Mohammad; Manglani, Hemlata; Galvão, Rosa; Varela, Miguel (Journal of Ecohumanism, 2024)
This study aimed to assess the impact of Self Help Groups and their specific interventions, such as vocational training programmes and the use of loans in productive means, on the empowerment of Dalit women of Haryana. A selected control group from OBCs was studied, and it was shown how the livelihood interventions of Self Help Groups bridged the gap between SC (Dalit) and OBC women beneficiaries. The study selected four districts from Haryana with an equitable distribution of SC and OBC women beneficiaries and 360 respondents with equal distribution of SC and OBC women beneficiaries from Haryana and used a Likert scale data for the analysis. Principal component analysis (PCA) and treatment effects were carried out using the propensity score matching method (PSM), the composite index for women’s economic empowerment was inferred, and important empowerment factors were identified in Haryana. Results compared and contrasted the implications for different social groups and districts selected for the study and concluded that Self Help Group interventions significantly affected the women empowerment of both social groups and uplifted the Dalit women beneficiaries to the level of OBC women in Haryana. A large number of training programmes are to be conducted to promote more small businesses and micro-enterprises.